PAROXYSMAL ATRIAL FIBRILLATION: CHOICE OF CARDIOVERSION THERAPY - B. A. Tatarskii (Рациональная фармакотерапия в кардиологии)
Characteristics and classification of different patterns of paroxysmal atrial fibrillation are presented. Main indications to restoration of sinus rhythm are discussed. The features of main medications used to terminate of atrial fibrillation are given. The choice of antiarrhythmic drug is considerate. Necessity of individual approach to therapy tactics is proved.